The Doc and the Duchess : The Life and Legacy of George H. A. Clowes - Clowes, Alexander W., 1946-2015 (Book collections on Project MUSE., 2016)
George Henry Alexander Clowes was a pivotal figure in the development of the insulin program at the Eli Lilly Company. Through his leadership, scientists and clinicians at Lilly and the University of Toronto created a unique, international team to develop and purify insulin and take the production of this life-saving agent to an industrial scale. This biography, written by his grandson, presents his scientific achievements, and also takes note of his social and philanthropic contributions, which he shared with his wife, Edith. It tells the story of Clowes from his childhood in late Victorian England to his death at Woods Hole on Cape Cod in 1958. Educated in England and Germany, Clowes came to America to join a startup laboratory in Buffalo, where he conducted basic research on cancer and applied research on other disease-related problems. Assuming the position of head of research at Lilly, Clowes was at the center of one of the great discoveries that changed the course of medical history and offered new life to millions of individuals with diabetes and other metabolic disorders. Clowes was also instrumental in the development of other commercial pharmaceutical advances. Devoted to a number of philanthropic causes, Clowes and Edith contributed greatly to the cultural life of his adopted country, a contribution that continues to this day.